From Project to Program: Tupange's Experience with Scaling Up Family Planning Interventions in Urban Kenya. Issue 45 (May 2015) - Keyonzo, Nelson; Nyachae, Paul; Kagwe, Peter; Kilonzo, Margaret; Mumba, Feddis; Owino, Kenneth; Kichamu, George; Kigen, Bartilol; Fajans, Peter; Ghiron, Laura; Simmons, Ruth
Abstract: This paper describes how the Urban Reproductive Health Initiative in Kenya, the Tupange Project (2010-2015), successfully applied the ExpandNet approach to sustainably scale up family planning interventions, first in Machakos and Kakamega, and subsequently also in its three core cities, Nairobi, Kisumu and Mombasa. This new focus meant shifting from a "project" to a "program" approach, which required paying attention to government leadership and ownership, limiting external inputs, institutionalizing interventions in existing structures and emphasizing sustainability. The paper also highlights the project's efforts to prepare for the future scale up of Tupange's interventions in other counties to support continuing and improved access to family planning services in the new context of devolution (decentralization) in Kenya.